The DosR regulon of Mycobacterium avium and adaptation to hypoxia - Belardinelli, Juan M.; Avanzi, Charlotte; Martin, Kelsey E.; Lam, Ha; Dragset, Marte S.; Wheat, William H.; Podell, Brendan K.; Gonzalez-Juarrero, Mercedes; Jackson, Mary (Frontiers in Cellular and Infection Microbiology, 2025)
Like other tuberculous and nontuberculous mycobacterial pathogens of human lung such as Mycobacterium tuberculosis and M. abscessus, M. avium is likely exposed to a variety of stressors during infection, including hypoxic conditions inside activated macrophages and in the avascular necrotic regions of granulomas. How M. avium survives hypoxic stress to establish a chronic infection is currently not well understood. Using RNA-sequencing, we here show that M. avium grown under progressive microaerophilic conditions activates more than 4-fold a subset of 16 genes, the expression of 13 of which is dependent on the two-component system regulator DosRS. A subset of M. avium DosR regulon genes was confirmed to also be activated upon exposure to nitric oxide. Although a second sensor kinase besides DosS has been proposed to function with the transcriptional regulator DosR in M. avium, we show that this other kinase cannot compensate for a deficiency in DosS. Loss of dosRS expression in M. avium led to a significant reduction in viability under hypoxia that was more marked at acidic than at neutral pH. Unlike the situation in M. abscessus, however, loss of DosRS did not significantly impact the ability of M. avium to establish a drug tolerant state in vitro or form biofilms under host relevant conditions. Collectively, these results are suggestive of a lesser impact of DosRS on the ability of M. avium to develop antibiotic tolerance compared to other nontuberculous mycobacteria. The M. avium dosRS mutant further showed no signs of virulence attenuation in murine macrophages and in chronically infected immunocompetent BALB/c mice.